Estimation of real-time remaining shelf life using mean kinetic temperature. (December 2020) - Kim, Jiyoung; Santos, Christian Ariane; Kim, Byeong-Sam; Kim, Jonghoon; Koo, Junemo
Abstract: An easy estimation method for remaining shelf life based on food temperature history is presented. The impact of varying temperature history to a given time on food quality can be expressed by the mean kinetic temperature (MKT) as a single temperature effect. MKT is calculated by applying the linear interpolation method to constant storage temperature and food quality data at the time of estimation. The remaining shelf life could be point-estimated, assuming the future temperature to be consistent at MKT. The extreme temperatures experienced by the food are used as the future temperature to predict the range of remaining shelf life. The differences in remaining shelf life estimations using mean kinetic, minimum, and maximum temperatures at a given time increased initially and decreased to zero as they approached the food shelf life. This decrease indicates that the accuracy of the remaining shelf life improves as it reaches the food shelf life when the accuracy is most important. The developed method is applied to packaged chicken and low-temperature-pasteurized milk and is validated. The developed methodology could be applied to other foods as long as their food quality index change could be described as kinetic models. Highlights: Shelf life is estimated easily using the mean kinetic and extreme temperature concepts. MKT should be lower than the recommended storage temperature for food freshness. MKT is a good value to represent the future food temperature to estimate shelf life. The accuracy of the shelf life estimation improves approaching the shelf life. The method is tested with chicken meat and milk and applicable to other foods.